Novel matrine derivative MD-1 attenuates hepatic fibrosis by inhibiting EGFR activation of hepatic stellate cells - Yi Feng; Hai-yan Ying; Ying Qu; Xiao-bo Cai; Ming-yi Xu; Lun-gen Lu (Protein & Cell, 2016)
Abstract Matrine (MT), the effective component of Sophora flavescens Ait, has been shown to have anti-inflammation, immune-suppressive, anti-tumor, and anti-hepatic fibrosis activities. However, the pharmacological effects of MT still need to be strengthened due to its relatively low efficacy and short half-life. In the present study, we report a more effective thio derivative of MT, MD-1, and its inhibitory effects on the activation of hepatic stellate cells (HSCs) in both cell culture and animal models. Cytological experiments showed that MD-1 can inhibit the proliferation of HSC-T6 cells with a half-maximal inhibitory concentration (IC50) of 62 μmol/L. In addition, MD-1 more strongly inhibits the migration of HSC-T6 cells compared to MT and can more effectively induce G0/G1 arrest and apoptosis. Investigating the biological mechanisms underlying anti-hepatic fibrosis in the presence of MD-1, we found that MD-1 can bind the epidermal growth factor receptor (EGFR) on the surface of HSC-T6 cells, which can further inhibit the phosphorylation of EGFR and its downstream protein kinase B (Akt), resulting in decreased expression of cyclin D1 and eventual inhibition of the activation of HSC-T6 cells. Furthermore, in rats with dimethylnitrosamine (DMN)-induced hepatic fibrosis, MD-1 slowed the development and progression of hepatic fibrosis, protecting hepatic parenchymal cells and improving hepatic functions. Therefore, MD-1 is a potential drug for anti-hepatic fibrosis.